A Mossbauer Spectroscopy Investigation of Fe enriched WC-Co - Sufianu, Adeleke Wasiu (My University, 2016)
Tungsten carbide cobalt (WC-Co) cemented carbides are widely used for cutting, drilling, machining and as wear resistant materials due to the combination of high hardness and fracture toughness. In this work, we report on as-milled and as-sintered WC-10Co-20Fe samples which were ball milled for 15 hrs and sintered using liquid phase sintering (LPS). These samples were investigated by Vickers hardness test, microstructural analysis, X-ray diffraction (XRD), transmission Mössbauer spectroscopy (TMS) and conversion electron Mössbauer spectroscopy (CEMS) techniques. A mean hardness value of 1160 ± 42 HV was obtained for WC-10Co sample while a value of 776 ± 35 HV was determined for the WC-10Co-20Fe using the Vickers hardness tester. The lower hardness value for WC-10Co-20Fe is attributed to the high volume of the binders (10% Co and 20 %Fe) incorporated in the sample. The microstructural analysis of the as-sintered WC-10Co and WC-10Co-20Fe samples reveals that the light regions represent the WC phases and the dark regions signify the presence of the Co and CoFe phases in the as-sintered WC-10Co and WC-10Co-20Fe samples, respectively. The energy dispersive spectroscopy (EDS) of the as-sintered samples shows the presence of the starting powders used (WC, Co and Fe) and some Cr contamination resulting from either the production process or the starting powders.
A dissertation submitted to the Faculty of Science, University of the Witwatersrand, Johannesburg, in fulfilment of requirements for the degree of Master of Science. May 2016.
Keywords: Mossbauer spectroscopy; Tungsten carbide-cobalt